2013
DOI: 10.1155/2013/938751
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Therapies in Allergic Rhinitis

Abstract: Objective. To determine the prevalence of herbal treatment of allergic rhinitis. Methods. In this prospective study, patients who were diagnosed with perennial allergic rhinitis were questioned about their use of natural products/herbal therapies for their symptoms. Results. In total, 230 patients were enrolled. Overall, 37.3% of the patients stated that they had used natural products/herbal therapies at least once. Women were more likely than men to use herbal supplements (38.3% versus 32.4%). Ten different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In addition, Spirulina may be useful for the treatment of allergic conditions [ 3 , 4 , 5 ]. A prospective study found a high prevalence of Spirulina usage for the relief of allergic rhinitis symptoms in Turkey [ 6 ]. On the other hand, polysaccharides contained in Spirulina also have immunostimulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Spirulina may be useful for the treatment of allergic conditions [ 3 , 4 , 5 ]. A prospective study found a high prevalence of Spirulina usage for the relief of allergic rhinitis symptoms in Turkey [ 6 ]. On the other hand, polysaccharides contained in Spirulina also have immunostimulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…We documented 63 plant species belonging to 40 botanical families, mainly the Asteraceae, Euphorbiaceae and Malvaceae used by Bapedi THs to treat rhinitis and related symptoms. Kanakavalli et al16 reported the dominant of Fabaceae , and Sayin et al15 found that all the botanical families in their study were each equally represented by a single species. The dominance of Asteracea , Malvaceae and Euphorbiaceae in our study could be attributed to their wider distribution across the studied sites, which in turn afforded local THs with higher diversity of plants to explore healing potential, and subsequently experiment against various human ailments including rhinitis.…”
Section: Discussionmentioning
confidence: 81%
“…As a matter of fact, there is generally a scanty of information regarding the use of herbal remedies to treat these conditions worldwide. However, few attempts to address this gap in knowledge have been made in countries such as Turkey15 and India16. Comparison of medicinal plants documented in these two studies with ours is divergent, probably due to the fact that diverse cultures of the world possess their own specific knowledge of plant use and tradition21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite availability of modern treatments, it is still common to trust the use of plants to treat rhinitis 7,8 . However, the mechanism of medicinal plants used to treat allergic rhinitis is unknown.…”
mentioning
confidence: 99%